UJI TOKSISITAS DARI EKSTRAK LAMUN JENIS Thalassia hemprichii DARI PERAIRAN KALASEY DENGAN MENGGUNAKAN METODE BRINE SHRIMP LETHALITY TEST - Faradila Y. Karim; Nickson J Kawung; Billy Th. Wagey (JURNAL PESISIR DAN LAUT TROPIS, 2019)
ABSTRACTBioactive compounds that are suspected of having anticancer activity are first tested for activity by means of a toxicity test. The purpose of this test is to obtain data on the ability of the activity of a bioactive compound to kill cells at small doses so as to obtain a lethal concentration or lethal data. These two measurements are often called LC50 or LD50, concentrations that can kill 50% of test animals. This study aims to test the cytotoxic activity of Thalassia hemprichii seagrass extract using the Brine Shrimp Lethality Test (BSLT) method.The results of the study showed that the mortality of Artemia salina larvae was influenced by the concentration of the test, meaning that the higher the concentration the more test animals died. Furthermore, the results of the probit analysis contained the toxicity activity of bio active compounds from seagrasses where the LC50 was 3.95 mg / l. A substance is declared to have the potential for cytotoxic activity if it has a value of LC50 at concentrations <1000 ppm for extracts and at concentrations <30 ppm for a compound.Â Keywords: Cytotoxic Activity, Thalassia hemprichii, Brine shrimp Lethality Test (BSLT)Â Â